Legal Protecting For Investors Forex Margin Trading Transactions In Futures Trading - Fadilla Azaria, Putri Andini; Apriani, Rani (International Journal of Education, Information Technology, and Others, 2023)
In the era of globalization, society's needs are increasing day by day. Because of this, many people from the upper middle class invest their wealth in the hope of making a profit to meet their needs. Forex is included in the futures exchange which is a derivative investment from the type of stock investment. The forex market is a market that sells one country's currency against another country's currency. Forex transaction activities are also included in the commodity futures market which is a futures trading contract and is supervised by Badan Pengawas Perdagangan Berjangka Komoditi (BAPPEBTI). Brokers act as intermediaries who bring together sellers and buyers of certain currencies. Brokers have direct access to dealers and banks that carry out forex trading throughout the world in order to carry out their duties properly. Futures brokers are regulated in Law Number 32 of 1997 concerning Commodity Futures Trading, especially in Article 31 paragraph (1) and Government Regulation Number 9 of 1999 concerning the Implementation of Commodity Futures Trading Article 37. Currently, some people's confidence in investing is still low because the large number of people interested in investing has become a place for irresponsible people to commit fraud by posing as forex brokers. In forex margin trading transactions by broker companies, the implementation of legal protection has not been able to fully accommodate the interests of investors. Law Number 32 of 1997 only regulates the resolution of disputes and does not mention further about the forms of legal protection efforts that must be taken by Futures Brokers